2004
DOI: 10.1021/cg049675u
|View full text |Cite
|
Sign up to set email alerts
|

Clathrate Hydrate Crystal Growth in Liquid Water Saturated with a Guest Substance:  Observations in a Methane + Water System

Abstract: This paper reports on a visual study of formation and growth of clathrate hydrate crystals in liquid water saturated (prior to hydrate formation) and in contact with methane gas under the pressure of 6−10 MPa at a temperature of 273.5 K. Irrespective of the pressure set in the experimental system, in most of the experimental runs we observed that a hydrate film first formed to intervene between methane gas and liquid water, and then hydrate crystals grew in liquid water from the hydrate film. Distinct variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
116
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 20 publications
15
116
1
Order By: Relevance
“…The further growth of hydrate is controlled by mass transfer of water or hydrate former through the film. Many experimental and/or theoretical studies on the growth of hydrate film have been carried out by several groups (Freer et al, 2001;Ma et al, 2002;Mochizuki and Mori, 2006;Mori, 2001;Ohmura et al, 2000Ohmura et al, , 2005Peng et al, 2007Peng et al, , 2008Peng et al, , 2009Saito et al, 2010Saito et al, , 2011Sun et al, 2007;Taylor et al, 2007;Uchida et al, 1999Uchida et al, , 2002, including the morphology of hydrate film, the growth rate of hydrate film, the thickness of hydrate film, the mechanism of hydrate film growth, and so on. However, so far it is still a controversial topic on the growth mechanism of hydrate film.…”
Section: Heat Transfer In Growth Of Hydrate Filmmentioning
confidence: 99%
“…The further growth of hydrate is controlled by mass transfer of water or hydrate former through the film. Many experimental and/or theoretical studies on the growth of hydrate film have been carried out by several groups (Freer et al, 2001;Ma et al, 2002;Mochizuki and Mori, 2006;Mori, 2001;Ohmura et al, 2000Ohmura et al, , 2005Peng et al, 2007Peng et al, , 2008Peng et al, , 2009Saito et al, 2010Saito et al, , 2011Sun et al, 2007;Taylor et al, 2007;Uchida et al, 1999Uchida et al, , 2002, including the morphology of hydrate film, the growth rate of hydrate film, the thickness of hydrate film, the mechanism of hydrate film growth, and so on. However, so far it is still a controversial topic on the growth mechanism of hydrate film.…”
Section: Heat Transfer In Growth Of Hydrate Filmmentioning
confidence: 99%
“…Such an assumption is neither unrealistic nor opportunistic. In general, hydrate crystals tend to grow thicker for lower levels of the driving force (DT or the guest-in-water concentration difference) for crystal growth [2,9,10]. For example, Ohmura et al [2] reported, based on their interferometric measurements, thicker R-134a hydrate films at lower DT levels than at higher DT levels.…”
Section: Comparison Between Predictions and Observationsmentioning
confidence: 99%
“…If the water had been saturated with the guest gas beforehand, the hydrates grew into the liquid water in various morphologies such as dendrites, columns, etc. [24][25][26][27] There are several observational studies that have reported the hydrate crystal morphology formed at the gas/liquid interface [28][29][30][31][32] and in the liquid water saturated with the guest gas. [24][25][26][27] They revealed that the crystal morphology and the propagation rate of the hydrate film depended on driving force, such as the system subcooling DT sub , the difference of the system temperature from the gas-hydrate-water equilibrium temperature corresponding to the system pressure.…”
Section: Introductionmentioning
confidence: 99%